Comparative transcriptome and metabolome profiles of the leaf and fruits of a Xianjinfeng litchi budding mutant and its mother plant - Xu, Ning; Qin, Xian-quan; Li, Dong-bo; Hou, Yan-jie; Fang, Chen; Zhang, Shu-wei; You, Jing-yi; Li, Hong-Li; Qiu, Hong-ye (Frontiers in Genetics, 2024)
Litchi (Litchi chinensis) is an important sub-tropical fruit for Chinese horticulture market. Breeding for improved fruit characteristics is needed for satisfying consumer demands. Budding is a sustainable method for its propagation. During our ongoing breeding program, we observed a litchi mutant with flat leaves and the fruit peel cracking of the mutant is sharp in comparison to curled leaves and blunt fruits of mother plant. To understand if these two organs contain useful differences or not, we performed a combined metabolome and transcriptome analysis. We identified 1060 metabolites in litchi leaves and fruits, of which, 106 and 101 were differentially accumulated between the leaves and fruits, respectively. Mutant leaves were richer in carbohydrates, nucleotides, and phenolic acids, while, the mother plant was rich in most of the amino acids and derivatives, flavonoids, lipids and organic acids and derivatives, and vitamins. Contrastingly, mutant fruits had higher levels of amino acids and derivatives, carbohydrates and derivatives, and organic acids and derivatives. However, mother plants fruits contained higher levels of flavonoids, scopoletin, amines, some amino acids and derivatives, benzamidine, carbohydrates and derivatives, and some organic acids and derivatives. The number of differentially expressed genes were consistent with the metabolome profiles. GO and KEGG pathway enriched genes' expressions showed consistent profiles as of metabolome analysis. These results provide groundwork for breeding litchi for fruit and leaf traits that are useful for its taste and yield.